ANALISIS FAKTOR-FAKTOR MOTIVASI KERJA PEGAWAI PADA BAGIAN PENGELOLAAN BARANG MILIK DAERAH SETDA KOTA PONTIANAK - BRATA B11108141, INDRA DEWA (Jurnal Manajemen Update, 2015)
The purpose of the study was to determine the factors that affect the motivation of employees working in the area of property management (BPBMD) Secretariat Pontianak City.The method used in this research is Descriptive research method with survey forms and all employees of the research object BPBMD Secretariat Pontianak City totaling 30 people. To know the factors that influencing motivation officer job, then the technique of data analysis using Analysis Descriptive Statistics as tool its analysis. Variables studied consisted of salaries, work environment, labor relations, supervision, reward/praise, and the work itself.Of the results of this study can be seen that the salaries, work environment, labor relations, supervision, reward/praise, and the work itself are all factors that influence on employee motivation. This is because the high motivation that caused the company can develop, direct, and approaches or relationships between superiors and subordinates are veryÂ  good. Therefore, the company should look and promotes the interests of employees in order to increase the companyâ€™s goals. Keywords : work motivation